Desenvolvimento e aplicação de polímeros molecularmente impressos para pré-concentração, extração e detecção de compostos de interesse forense e ambiental - Silva, Weida Rodrigues (2024)
Molecularly Imprinted Polymers (MIPs) are synthetic polymeric materials designed for selective molecular recognition. The synthesis of MIPs involves the presence of the analyte during the polymerization process, creating binding sites that are complementary to the molecular structure of the analyte. Thus, MIPs can recognize and bind to the compounds of interest, reducing interference from other compounds in the analysis and improving the accuracy and reliability of the results. Therefore, MIPs have become an important tool in analytical chemistry, contributing to important steps in chemical analysis such as sample preparation, as well as being able to be used as receptors for chemical sensors. In this work, MIPs have been synthesized for application in three scenarios: (i) solid-phase extraction using a disposable pipette tip (MISPE with DPX) for the preconcentration of scopolamine in synthetic urine and determination by capillary electrophoresis; (ii) fabrication of a fluorescent sensor for the determination of captopril in water and urine samples; and (iii) preparation of paper MIPs (p-MIPs) for the extraction of naproxen using the polymerization-free method. The integrated MISPE method with DPX-CE achieved a preconcentration factor of 20 with a working range of 0.5 to 6 µM, a limit of detection (LOD) of 0.04 µM, a repeatability of 6.4%, and satisfactory recoveries for 2 µM and 6 µM of 84% and 101%, respectively. The determination of captopril was based on the decrease in fluorescence intensity caused by the interaction between the analyte and the fluorescent molecularly imprinted polymer (Si-FMIP). The material was synthesized using silica nanoparticles together with fluorescent monomers. The method demonstrated an LOD of 0.7 µM, repeatability of 5.4%, and adequate recoveries of 98.5%, 99.9%, and 99.2% at 1.5 µM, 3.5 µM, and 10 µM, respectively, for wastewater analysis over a working range of 1 to 15 µM. For synthetic urine samples, the method showed a range of 0.5 to 15 µM, an LOD of 0.4 µM, repeatability of 7.4%, and recoveries of 93.7%, 92.9%, 98.0%, for 1.5 µM, 3.5 µM, and 7.5 µM, respectively. PVDF, PVA and Nylon-6 were evaluated for preparing p-MIPs. Although there are still challenges to be overcome, such as optimizing the proportions of reagents, the results found in this study indicate a promising path for continuous improvement of this preparation approach. However, the presented MIPs illustrate the versatility of the application of these materials, from solid phase extraction to sensor fabrication, highlighting their relevance in sample preparation and detection of pharmaceutical compounds in biological and environmental environments.